2018
DOI: 10.3390/ijms19103155
|View full text |Cite
|
Sign up to set email alerts
|

BDNF, Brain, and Regeneration: Insights from Zebrafish

Abstract: Zebrafish (Danio rerio) is a teleost fish widely accepted as a model organism for neuroscientific studies. The adults show common basic vertebrate brain structures, together with similar key neuroanatomical and neurochemical pathways of relevance to human diseases. However, the brain of adult zebrafish possesses, differently from mammals, intense neurogenic activity, which can be correlated with high regenerative properties. Brain derived neurotrophic factor (BDNF), a member of the neurotrophin family, has mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 144 publications
(179 reference statements)
0
33
0
4
Order By: Relevance
“…In zebrafish, evaluating BDNF's role in adult neurogenesis and brain regeneration is a nascent field. Only a few recent studies have reported the likely involvement of BDNF/TrkB system in mediating reparative brain regeneration (reviewed in (Cacialli, Palladino, & Lucini, ) and (Lucini, D'Angelo, Cacialli, Palladino, & de Girolamo, )). Inducing an injury in the mid‐dorsal region of the right telencephalic hemisphere in zebrafish causes a dramatic increase in the proliferation of neural progenitors.…”
Section: Bdnf In Adult Neurogenesismentioning
confidence: 99%
“…In zebrafish, evaluating BDNF's role in adult neurogenesis and brain regeneration is a nascent field. Only a few recent studies have reported the likely involvement of BDNF/TrkB system in mediating reparative brain regeneration (reviewed in (Cacialli, Palladino, & Lucini, ) and (Lucini, D'Angelo, Cacialli, Palladino, & de Girolamo, )). Inducing an injury in the mid‐dorsal region of the right telencephalic hemisphere in zebrafish causes a dramatic increase in the proliferation of neural progenitors.…”
Section: Bdnf In Adult Neurogenesismentioning
confidence: 99%
“…The highest upregulation was observed for bdnf ( Fig 3D). From single-cell analyses, we found that bdnf was predominantly expressed in neuronal clusters (90% in neurons and 8% in glial cells; Fig 3E, S4H Fig), whereas its receptor ntrk2 [37,38] was expressed mainly in neurons (68% neuronal and 28% glia; Fig 3E, S4H Fig), and another BDNF receptor ngfra [37][38][39] was mostly glial (93% in glia and 5% in neurons; Fig 3E; S4H Fig). Therefore, we hypothesized that 5-HT dependent regulation of bdnf expression might signal to the glial cells through ntrk2 and ngfra in the adult zebrafish brain.…”
Section: Introductionmentioning
confidence: 96%
“…The mammalian and zebrafish behavioral paradigms are in close parallel suggesting the evolutionarily conserved nature of many behaviors across species [3,5,11]. Despite neuroanatomical differences between the mammals and teleosts, evidence shows homologous functions in several key zebrafish brain areas [12,13,14,15]. The recent emergence of high-throughput tracking of zebrafish embryos and larvae has further bolstered the behavior research in the zebrafish field, making the research more objective, replicable, and efficient.…”
Section: Introductionmentioning
confidence: 99%